I'll Follow the Minority: The Effects of Sales Level on Purchase Intention of Self-expressive Products - Wan, Xiaoyu; Wang, Tingyi; Wu, Jifei (Frontiers in Psychology, 2018)
The present study focuses on the naive theory of exclusivity (vs. popularity) triggered by the sales level of self-expressive (vs. functional) products and introduces perceived self-image exclusivity and perceived face threat to explain the effect of self-expressive products’ sales levels on consumers’ purchase intention. Specially, about nine hundred young people participated in four experiments, which used T-shirts, pillows, cups, fashion coats and heating blankets as experimental materials. Through four studies, it is found that consumers are more likely to choose self-expressive (vs. functional) products with low sales (vs. high sales) level. In addition, the paper presents a serial mediation effect of perceived self-image exclusivity → perceived face threat, which can explain the "I will follow the minority" effect of self-expressive products. Finally, the study presents the theoretical and practical significance and future research direction.